Anti-snake venom and analgesic activities of extracts and betulinic and oleanolic acids isolated from Parinari curatellifolia - Emmanuel Mshelia Halilu; Natasha October; Chinenye J. Ugwah-Oguejiofor; Amina Yusuf Jega; Mathias Sylvester Nefai (AOSIS, 2020)
Background: Parinari curatellifolia is used in Nigeria by traditional medicine practitioners (TMPs) for the treatment of snakebite and other conditions. Aim: This study is aimed at evaluating the anti-snake venom (ASV) and analgesic activities of n-hexane, ethyl acetate and methanol extracts as well as that of betulinic and oleanolic acids. Setting: The extracts and the isolates were subjected to acute toxicity studies, anti-snake venom and analgesic activities. Methods: Acute toxicity studies for the extracts were performed according to Lorke's method whilst that of betulinic and oleanolic acids were performed according to Organization for Economic Co-operation Development 425 at the limit dose of 2000 mg/kg in mice. The ASV activity of the extracts and the betulinic and oleanolic acids were screened against Naja nigricollis venom phospholipases using the phospholipase-A2 acidimetric assay. The analgesic activity of ethyl acetate extract (35 mg/kg, 70 mg/kg, 140 mg/kg), betulinic acid (1 mg/kg, 5 mg/kg, 10 mg/kg) and oleanolic acid (1 mg/kg, 5 mg/kg, 10 mg/kg) were evaluated using acetic acid-induced abdominal constrictions in mice. Results: The LD50 of the methanol and ethyl acetate extracts were 113 mg/kg and 471.17 mg/kg, respectively, whilst that of the betulinic and oleanolic acids were greater than 2000 mg/kg. In the ASV study, the extracts inhibited the hydrolytic action of phospholipases with a percentage inhibition of 24.1% (n-hexane), 29.3% (ethyl acetate) and 20.7% (methanol), whilst the ASV (standard) caused 72.9% inhibition. On the other hand, the betulinic and oleanolic acids inhibited the hydrolytic action of phospholipases with a percentage inhibition of 35.6% and 31.4% respectively. For the analgesic evaluation, the ethyl acetate extract exhibited analgesic activity by producing a significant (p 0.05) reduction in the number of writhes (7.75 ± 1.20, 11.82 ± 3.10 and 14.98 ± 2.72) at 140 mg/kg, 70 mg/kg and 35 mg/kg, respectively. Betulinic acid at 10 mg/kg, 5 mg/kg and 1 mg/kg showed a mean number of writhes of 3.40 ± 0.8, 4.20 ± 1.4 and 5.60 ± 2.1, respectively. Oleanolic acid at 10 mg/kg and 5 mg/kg also showed 7.50 ± 2.6 and 6.40 ± 1.8 mean number of writhes. Conclusion: This study has validated scientifically why P. curatellifolia is used traditionally in the treatment of snakebite, as the ethyl acetate extract and the isolated compounds moderately inhibited the hydrolytic action of phospholipase-A2. Also, betulinic and oleanolic acids exhibited analgesic activity in acetic acid-induced writhing in mice.